Patterns of Counselling-related Problems in a Malaysian Corporate Setting - Mohamed, Othman; Musa, Muhaini (Universiti Putra Malaysia Press, 1994)
Categories of counselling related problems in a corporation were identified. Subsequently, a comparative analysis was initiated differentiating the problems according to age, gender and job position. The sample size in the study n =288 was determined with a power set at .8 and oc =.05, thus ensuring a reduction of Type II Error. Through frequency analysis, the result pattern showed that problems related with retirementwas highest (24.5%); career problems (16.1 %); personal problems (13%); family and marital problems (11.4%). Also, the results indicated that retirement problems showed a significant difference among age groups. The comparison between gender indicated a significant difference only on personal problems. There was no significant difference in all categories of problems between the executives and the non-executives.